2010
DOI: 10.1016/j.ejc.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

On topological relaxations of chromatic conjectures

Abstract: There are several famous unsolved conjectures about the chromatic number that were relaxed and already proven to hold for the fractional chromatic number. We discuss similar relaxations for the topological lower bound(s) of the chromatic number. In particular, we prove that such a relaxed version is true for the Behzad-Vizing conjecture and also discuss the conjectures of Hedetniemi and of Hadwiger from this point of view. For the latter, a similar statement was already proven in an earlier paper of the first … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…♦ Remark 3. A more sophisticated such variable as the ones mentioned in Remark 2 is a topological relaxation of the chromatic number in the sense of [45]. There are several closely related lower bounds on the chromatic number based on algebraic topology that all grew out from the pioneering work of Lovász in [32].…”
Section: On the Possibilities Of Equalitymentioning
confidence: 99%
See 1 more Smart Citation
“…♦ Remark 3. A more sophisticated such variable as the ones mentioned in Remark 2 is a topological relaxation of the chromatic number in the sense of [45]. There are several closely related lower bounds on the chromatic number based on algebraic topology that all grew out from the pioneering work of Lovász in [32].…”
Section: On the Possibilities Of Equalitymentioning
confidence: 99%
“…There are several closely related lower bounds on the chromatic number based on algebraic topology that all grew out from the pioneering work of Lovász in [32]. In [45] the topological lower bound involving the so-called co-index of the box complex of the graph at hand is considered as a graph parameter itself and it is shown that it also satisfies the Hedetniemi-type equality.…”
Section: On the Possibilities Of Equalitymentioning
confidence: 99%
“…The dual to Conjecture 1.6, namely coind(X × Y ) = min(coind(X), coind(Y )), has been considered by Simonyi and Zsbán [SZ10]. This statement is trivial in topology, that is, S n → Z 2 X × Y if and only if S n → Z 2 X and S n → Z 2 Y .…”
Section: Obstacles and Non-tidy Spacesmentioning
confidence: 99%
“…Hell [4] proved that if the topological bound is tight for all factors in a product of c-chromatic graphs, then the product is c-chromatic. (See also [10] for a contemporary treatment of the subject.) Problem 4.2.…”
Section: Proofmentioning
confidence: 99%